A data-based damping modeling technique. Issue 1 (1996) - Zhang Zhang, William William; Lee Lee, S. G. S. G.
Abstract : Damping mechanisms exist in all vibration systems, but their nature is little understood and there is no systematic method for modeling general damping. This paper describes a novel damping modeling method (the Method of Energy Approximation, or MEA). This method is novel because it is a unique damping modeling method without assumed damping linearity; it is based on experimental data instead of physical principles; hence it is applicable to vibration systems of various materials and configurations; and it is suitable for vibration system transient control. Among the three quantities essential to an understanding of the dynamics of a vibration system, mass, stiffness, and damping, the last is the most complex and least understood. Therefore, with recent technology advances in such areas as composite materials and smart materials, the need for a good damping modeling method is more urgent than ever.